Analysis of the School Environment's Influence on Student Learning Outcomes in Economics Subjects - Andriani, Lili (Information Technology and Science (ITScience), 2024)
The aim of this research is to analyze the influence of the school environment on learning outcomes in economics subjects. Education also functions to lead people to uncover the veil of life while placing themselves as actors in every change. This research was conducted basically to see the influence of the school environment on student learning outcomes using quantitative methods. The results of this research show that the school environment partially influences student learning outcomes in economics subjects. The conclusion of this research is that there is a linear relationship between the school environment and learning achievement at SMAN 11 Jambi City. The better the school environment will improve learning outcomes, conversely the worse the existing school environment, the more impact it will have on learning outcomes.